The Effect of Sodium Bikarbonate Immersion and Frying Temperature TowardThe Hardness Value of Cocoyam Chips (Xanthosoma sagittifolium) - Putranto, Angky Wahyu; Argo, Bambang Dwi; Komar, Nur (Jurnal Teknologi Pertanian, 2013)
The major problem that need to be considered in chips product arecrunchiness. The research to get the crispy chips product is generally done by adding a solution of Calcium Hydroxide (Ca(OH)2).However, basically high calciuminCalcium Hydroxide makes a hard texture. Therefore, searched alternatives to make a crunchy texture chips with a low hardness level. The immersion of Sodium Bicarbonate (NaHCO3) as crunchy maker, will produce CO2 gas which is expected to form many pores in cocoyam chips,so the texture of produced chips will be more crisp. To see the quality of chips due to the Immersion of Sodium Bicarbonate (NaHCO3), then do the microstructural studies using Scanning Electron Microscopy (SEM).The results obtained water content and hardness values are lower than previous research, and the best treatment was NaHCO3 soaked concentration of 1 g/L and the frying temperature of 180 Â°C with the parameters value such as physical parameters; watercontent of 2.636%, hardness value of 0.443 kg/cm2,organoleptic parameters; crunchiness of 6.05, the appearance of 5.30, taste of 5.45, colour 5.40 and the energy needed for frying are 55.323 kJ/kg. Microstructure from SEM showed that immersion of NaHCO3 and frying temperature effected to gelatinization which is characterized byincreasing the average of matrix diameter from 68.51Î¼m (raw material) to 103.07Î¼m and has a diameter bubbles on average 29.19 Î¼m (soaked of NaHCO3 with a concentration of 1 g/L and the frying temperature of 180 Â°C). Key words : Cocoyam, Sodium Bicarbonate, Scanning Electron Microscopy (SEM)